A Sociocultural Theory to Learning: Malaysia’s Experience - Abu Bakar, Norsuhaily; Puad Mat Som, Ahmad (International Journal of Engineering and Technology, 2018)
The study explores and analyses some of the challenges inherent to incorporating play into classroom practice, which occurs in two types of preschool classroom settings in Malaysia. It investigates the implementation of play in each of these settings. This study builds an understanding of the processes involved. It demonstrates a theory of learning that supports analysis of participation in social activity where participants work towards social goals within a view of learning being based on a cultural and collective foundation. The discussion is designed to convince the reader the value of the underpinning theory for this study and to explain the interpretive lens on learning through play that emerges. The approach recognizes that this interpretive lens offers a particular way of guiding the data collection and interpreting the data. In developing a conceptual framework for this study, it provides not only a way to interpret what is learning through play, but also to report the research findings within a sociocultural frame.